Factors of Influencing Health Workers in Providing Early Complementary Breastfeeding in dr. Iskak Hospital Tulungagung - Poppy Farasari; Indasah Indasah; Sentot Imam Suprapto (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2018)
Breast milk is the best food God creates for newborns. Artificial feeds for infants mixed using today's technology, were not able to match the benefits of breast milk. The purpose of the study was to analyze Factors affecting the Health Worker in giving the Early Breastfeeding in dr. Iskak Hospital Tulungagung. The research design used in the research is Analytical Observation. The population is health workers who have babies 6-12 months of age. The sample size was 67 respondents using Cluster Random Sampling technique. Independent variable of research is knowledge, distance, and family support. The dependent variable of the research is the early feeding of breast milk supplements. Data were collected by using questionnaire, then the data were analyzed by using logistic regression. The results showed that most have residence distance to the workplace as far as 3 KM as many as 44 respondents (65.7 %), most have good knowledge as many as 64 respondents (95.5 %) , most have high family support as much as 45 respondents (67.2%) , most respondents gave ASI without MP-ASI as much as 42 respondents (62,7%) . Statistical test results that Overall Statistics with a significance value of (p) 0, 000 which means that there are variables that affect the administration of MP-ASI and variable most affect family support with a value of (p) of 0.000. The conclusion of this study is family support affects in health workers in providing early breastfeeding in dr. Iskak Hospital Tulungagung.